Linguistic Inquiry Word Count and Deep Learning for Multimedia Analysis - SAYADI Rabia / SELMI Amina (university of eloued جامعة الوادي, 2024)
هذا العمل مخصص لدمج التحقيق اللغوي وعدد الكلمات مع تقنيات التعلم العميق لتحليل الوسائط المتعددة، والذي يتضمن الاستفادة من الرؤى اللغوية من التحليل القائم على النص ودمجها مع نماذج التعلم العميق القادرة على معالجة المحتويات المختلفة، بما في ذلك المحتوى الصوتي ومقاطع الفيديو. نعرض أولاً بعض المفاهيم والتعاريف المتعلقة بالقياس النفسي اللغوي. ثم نتحدث عن تحليل محتوى الوسائط المتعددة. This work is devoted to the integration of Linguistic Inquiry and Word Count (LIWC) with deep learning techniques for multimedia analysis, which involves leveraging the linguistic insights from text-based analysis and combining them with deep learning models capable of processing various modalities, including audio and videos. We first present some concepts and definitions related to psycholinguistic measurement. Then we talk about multimedia content analysis
memoier maste informatuque
Keywords: القياس النفسي، تحليل الوسائط المتعددة، التحقيق اللغوي وعدد الكلمات، تحليل النصوص، التعلم العميق، نماذج اللغة الكبيرة،; Psychometric; Multimedia Analysis; LIWC; Text Analysis; Deep learning; LLMs; Multimedia Content.